Wetted Bulb Dimensions From a Trickle Source - Elsa S. Sepúlveda; Fedro S. Zazueta (EDIS)
An estimation of the wetted bulb diameter dimensions is needed to determine the number of emitters per plant when using drip or trickle irrigation systems. It is generally recommended that a sufficiently large fraction of the root zone be wetted by irrigation to ensure adequate water and nutrient supply to the plant. This software allows the calculation of the wetted bulb diameter from a point source in a sandy soil. Please note that the method has not been tested or calibrated for soils other than sands. In addition the method applies only to deep homogeneous, uniform soils. This document is ABE351, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 22, 2004.